Time-specific multi-component foliar fertilization of rice for yield increase and blast control - Wan Talib, Wan Suhana (2018)
Balanced nutrition imposed at specific times of a plant’s critical growth stages is a key factor in achieving high yield and disease control. Efficient and rapid uptake of nutrients critically needed at a specific time can be deployed through foliar fertilization. The objective of this study is to investigate the effect of multicomponent foliar fertilizer application at different growth stages on rice yield and blast control. A glasshouse experiment was conducted in University Agriculture Park, Universiti Putra Malaysia in Serdang, Selangor. Field experiment on yield was performed in two different locations representing our major granary areas. The first area is classified as medium productivity district, namely, Muda Agriculture Development Authority (MADA) in Tunjang, Kedah whereas the second area is classified as low productivity district that is Integrated Agriculture Development Area (IADA) in Semerak Kemasin. Multi-component foliar fertilizer was applied at three different critical growth stages with different frequency of application for rice cv. MR 219. The different frequencies were deployed as: (T1) Two sprays at seedling stage (emergence of 2nd and 5th leaf); (T2) Three sprays at the seedling stage (two sprays: 2nd and 5th leaf) and tillering stage (single spray: active tillering day 35 DAS); (T3) Five sprays at the seedling (two sprays), tillering (single spray), and panicle stages (two sprays at panicle initiation: 45 DAS and panicle differentiation stages: 60 DAS). Results in glasshouse experiment showed increased growth, yield and yield component of rice. Significant increase was recorded in plant height (2.9%), leaf area index (114%), photosynthesis rate (23%), biomass (134%), 1000-grain weight (9.8%), number of tillers (71.8%), productive tillers (64%) and grain yield (59%). It is concluded that five foliar applications of multi-component foliar fertilizer at seedling stage (two sprays), tillering (single spray) and panicle (two sprays at panicle initiation and panicle differentiation) stages facilitate in enhancing yield and yield components of rice in the glasshouse experiment. Rice leaf blast was also reduced through five-time application of multi component foliar fertilizer by 87.36%. Results in field experiment in MADA area, in the district of Tunjang, Kedah showed increased growth, yield component and yield of rice. Significant increase was recorded in tiller number (47.5%), panicle length (11.42%), grain number (30.64%), grain filling (11.03%), grain weight (18.68%), biomass (22.80%) and yield (25.87%). Similarly, results in IADA area, Semerak Kemasin district showed increased growth and yield component. Significant increase was recorded in chlorophyll content SPAD value (7.83%), panicle length (15.17%), grain number (43.13%), grain filling (14.99%), grain weight (3.2%) and biomass (69.86%). It is concluded that the treatment 3 with five foliar applications of multicomponent foliar fertilizer at seedling (two sprays), tillering (single spray) and panicle (two sprays at panicle initiation and panicle differentiation) stages facilitate in enhancing yield and yield components of rice in the field experiment. Rice leaf blast was reduced by five-time application of multi-component foliar fertilizer. Based on these findings, farmers should be advised and guided according to critical growth stages in foliar fertilizer application. Timely application of foliar fertilizer is important to ensure sufficient supply of macroand micronutrients to supplement nutrients from soil applications for better plant growth and rice production. Concomitantly, foliar fertilization can be a useful pest management strategy among paddy farmers to prevent or lessen disease severity.